The modal analysis of a pipe elbow with realistic boundary conditions - Carneiro, J.O.
A vibration analysis for the determination of the natural frequencies and the associated eigenmodes of a pipe elbow with end-flanges or tangent terminations was performed. A numerical investigation of this problem was achieved with a semi-analytic definition finite ring element and a commercial finite element code. To assess the accuracy of the numerical solution for the elbow vibration, an experimental modal analysis was performed on a curved and on a straight pipe. The responses were processed by a data acquisition system which performs a fast Fourier transform on the time histories to convert them from a time to frequency domain, these leading to the extraction of natural frequencies and mode shapes associated with the test-specimen. The results were compared with the corresponding ones from the numerical approach and discussion about the results completes the paper.